Complement activation assessed by C3bc and C5b-9 terminal complex as diagnostic biomarkers for deep vein thrombosis - Vårin Eiriksdatter Wikan; Øyvind Øverli; Thor Ueland; Tom Eirik Mollnes; Sigrid Kufaas Brækkan; Annika Elisabet Michelsen; Gholamreza Jafari Yeganeh; John-Bjarne Hansen; Ellen Elisabeth Brodin (PLoS ONE, 2025)
Background The overuse of compression ultrasound procedures on patients with suspected deep vein thrombosis compromise the cost-effectiveness of deep vein thrombosis management and emphasize room for improvement of the current diagnostic algorithm. As the complement system and hemostasis are comprehensively intertwined, we aimed to investigate complement activation products as diagnostic tests for acute deep vein thrombosis alone or together with D-dimer. Methods We performed a cross-sectional study using consecutive sampling of outpatients referred to the emergency department with suspected first-time deep vein thrombosis of the lower limbs, to investigate the diagnostic utility of the index tests C3bc and C5b-C9 terminal complex (TCC) with compression ultrasound as reference standard. For comparison of receiver operating characteristics, analyses were also performed for D-dimer and C-reactive protein in addition to analyses for the index tests on a D-dimer positive patient subgroup. Results Of the 366 included patients, 103 had deep vein thrombosis. The calculated effect sizes of differences between groups (Cohen’s d) with 95% confidence intervals (95%CI) were 0.25 (95%CI 0.03–0.48) for C3bc, 0.33 (95%CI 0.09–0.57) for C5b-C9 terminal complex (TCC), 0.88 (95%CI 0.61–1.15) for C-reactive protein, and 1.64 (95%CI 1.37–1.91) for D-dimer. The areas under the curves derived from comparison receiver operating characteristics analyses with corresponding 95%CIs for C3bc, C5b-C9 terminal complex (TCC), C-reactive protein and D-dimer were 0.56 (95%CI 0.50–0.63), 0.64 (95%CI 0.58–0.69), 0.73 (95%CI 0.67–0.79) and 0.92 (95%CI 0.89–0.95), respectively. Conclusion The plasma levels of the complement activation products C3bc and C5b-C9 terminal complex (TCC) were elevated in patients with acute deep vein thrombosis but displayed low diagnostic performance for deep vein thrombosis alone or together with D-dimer.